Extracorporeal Detoxification Methods in the Treatment of Destructive Pancreatitis - E. L. Ismailov; S. N. Eralina; B. B. Tekesbaev; R. B. Abdrasulov (Общая реаниматология)
The rise in the incidence of acute necrotic pancreatitis in the past decade and high mortality rates of as high as 20—45% all suggest that the disease is of high social, medical, and economic importance.Objective: to study the efficiency of extracorporeal detoxification methods in the combination treatment of patients with severe destructive pancreatitis.Subjects and methods. The investigation enrolled 20 patients aged 40 to 53 years with destructive pancreatitis treated in the intensive care unit, Almaty City Clinical Hospital Four.Results and discussion. Analysis of the findings over time could reveal that early incorporation of extracorporeal detoxification methods in the combination treatment of pancreatic necrosis provides a reduction in the clinical signs of endotoxicosis, which could prevent anuric acute renal failure in 61% of the cases and completely safeguard against multiple organ dysfunction in 22%. The investigation showed the necessity and efficiency the early use of albumin dialysis, hemodiafiltration in the combination treatment of sepsis and septic shock in destructive pancreatitis, leading to a significant reduction in mortality rates. The maximum detoxification potential of albumin dialysis in sepsis complicating the course of destructive pancreatitis is achieved by a combination of different mechanisms for elimination of toxic substances, such as convection, sorption, and diffusion, in the extracorporeal circuit.Conclusion. Early use of extracorporeal detoxification methods in patients with severe destructive diseases of the pancreas results in a significant reduction in mortality rates.